Comparing Static Analysis of Earth Dam Strength with Space Monitoring Data - Salyamova Klara; Tashmatov Komiljon; Nishonov Nematilla; An Ekaterina (E3S Web of Conferences)
This study focuses on the stress-strain behavior of a shallow earth dam, using the Kattakurgan reservoir in Uzbekistan as a case study. The analysis examines the primary forces acting on the dam, specifically gravity forces and hydrostatic pressure. The problem is addressed using a plane elastic statement through the numerical finite element method. The results from the calculations highlight the most vulnerable areas of the dam, particularly at the base of the upstream slope. Theoretical findings align with data obtained from space monitoring. Additionally, the study identifies regions of maximum uplift, settlement, and average annual displacement for both the entire reservoir area and the dam itself.